2012
DOI: 10.1158/0008-5472.can-12-0688
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in miRNAs Predict Bladder Cancer Risk and Recurrence

Abstract: miRNAs play important roles in numerous cellular processes, including development, proliferation, apoptosis, and carcinogenesis. Because altered expression and function of miRNAs has been observed in bladder cancer, we investigated whether genetic variations in miRNAs are associated with bladder cancer risk and prognosis. Using bioinformatics tools, we selected five single-nucleotide polymorphisms located in miRNAs and used these to evaluate miRNA-disease associations in a two-stage model, consisting of 1,019 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 51 publications
4
65
0
Order By: Relevance
“…However, in a large screen of effective genetic variants in microRNAs (miRNAs) in bladder cancer, TRAF6 was hypothesized as an effector molecule of miR-146a. miR-146a has an notable role in predicting the risk and recurrence of bladder cancer (30). This supported the results in the present study, which indicated that TRAF6 expression may be a prognostic factor in urothelial bladder cancer.…”
Section: Univariate Analysissupporting
confidence: 92%
“…However, in a large screen of effective genetic variants in microRNAs (miRNAs) in bladder cancer, TRAF6 was hypothesized as an effector molecule of miR-146a. miR-146a has an notable role in predicting the risk and recurrence of bladder cancer (30). This supported the results in the present study, which indicated that TRAF6 expression may be a prognostic factor in urothelial bladder cancer.…”
Section: Univariate Analysissupporting
confidence: 92%
“…Most of the samples included in this study had been enrolled in previous association studies (17)(18)(19)(20). All of the subjects were unrelated ethnic Han Chinese.…”
Section: Study Populationsmentioning
confidence: 99%
“…Grading and staging were conducted in accordance with the 2004 WHO/ ISUP classification of bladder cancer. For additional follow-up, we collected 226 patients with non-muscle invasive bladder cancer from the Huai-An Hospital (Nanjing, China) starting in May 2005, as described in our previous study (17). Every 3 months, follow-ups were conducted by telephone.…”
Section: Study Populationsmentioning
confidence: 99%
“…The authors proposed that the SNP could be correlated with the transition from normal to neoplastic thyroid tissue (23). It is worth mentioning that rs2910164 has been later shown to predispose to hepatocellular carcinoma in males (31), prostate cancer (32), bladder cancer (33), and colorectal cancer (34). Rs2910164 is also proposed to contribute to the pathogenesis of breast and ovarian cancer, as the target genes of miR-146a include BRCA1 and BRCA2.…”
Section: Microrna-mediated Thyroid Cancer Riskmentioning
confidence: 99%